How mobile augmented reality applications affect continuous use and purchase intentions: A cognition-affect-conation perspective. (November 2021) - Qin, Hong; Osatuyi, Babajide; Xu, Lu
Abstract: Augmented reality (AR) is rapidly gaining attention in practice, and research as the adoption of smartphones and technological advancements persist. The focus of current literature on AR has been on its use for improving visual and display quality. However, limited guidance is offered on how consumers evaluate their experience and how that, in turn, influences their behaviors, especially in the smartphone context. This study seeks to extend this line of research by applying the cognition-affect-conation framework to examine how mobile augmented reality (MAR) experiences shape the consumer decision-making process. Data collected from 316 users in the United States were analyzed using partial least squares structural equation modeling (PLS-SEM). The results reveal that consumers' cognitive evaluation of MAR applications stimulates their affective reactions, which eventually create conative behaviors. Thus, this study offers an integrated perspective for investigating continuous use and purchase intentions jointly in one research model. In addition, it examines how perceived value, a cognitive trait variable, influences consumer conative responses directly and indirectly through affective responses. The results confirm the relationships proposed in the cognition-affect-conation framework and empirically support the direct and indirect influence of perceived value on conative efforts in the MAR context. The findings contribute to AR theory building, application design, and marketing strategy development.